Best Paellas & Rice Recipes in Málaga. - Sánchez-Gómez, Fernando (Autoedición en Amazon Books, 2016)
Rice, the guiding light and the star of flavours in the healthy Mediterranean diet, is the central meeting point for the great food products of Malaga. In this book you will find more than 200 different ways to cook rice according to the experts of the Malaga food sector. The excellent food products in our rich and varied pantry are the supporting actors; meat, fish and seafood; fresh fruits and vegetables; dried fruits and legumes. These rice dishes are cooked with the exquisite extra virgin olive oil and paired with the well-known wines produced in Malaga and its Sierras. The recipes are classifed by chapters according to their preparation: moist, extra moist, paellas, risottos, sushis, other versions and desserts take the reader plate by plate, glass by glass through the culinary treasures and the art of wine-making of the whole province: Axarquía, Ronda, Nieves mountain range, the farmlands of Antequera, the north-eastern corner known as Nororma, the Guadalhorce valley, the Montes, hills surrounding the city, the Costa del Sol and the ports from Estepona to La Caleta. The Rice of Malaga is also a food guide to Malaga and its province and provides information on the restaurants, whatever their star classification where the rice dishes may be eaten: there are restaurantes with Michelin stars and without, country eating places, taverns, seafood specials, beach restaurantes, cafeterias, bars and gastrobars, cake shops, hotel restaurants and hotel schools.... If there is a good rice dish on the menu, you will find the recipe here, directly from the chef that made it famous for you to try at home.
Keywords: Cocina malagueña; Arroz - Recetas de cocina; Rice; Recipes; Malaga's Cuisine; Paellas in Malaga; Arroces de Málaga; Pairing of Malaga and Sierras de Málaga wines